Distribution Route Making for Mushroom Harvest Using Artificial Bee Colony Method - Ari Santosa, I Made (Universitas Negeri Semarang, 2020)
Mushrooms are food ingredient that is currently favored by the public. Seeing the large demand for mushrooms, many mushroom businesses have developed. The high level of demand for mushrooms by consumers in different locations results in the high time and costs spent in distributing mushrooms. In addition, determining distribution routes in mushroom marketing is still done manually based on the sender's knowledge, therefore reduces the effectiveness and efficiency of mushroom marketing because the distribution routes used are not optimal. To overcome these problems, it is necessary to determine an effective and efficient distribution route to reduce distribution costs and speed up distribution time. Based on these problems, this research uses the Artificial Bee Colony (ABC) method in determining the distribution route of mushroom harvest. The purpose of this study was to apply the ABC method in determining the distribution routes of mushroom harvest. The result of this research is a visualization of mushroom distribution routes using the ABC method, so it can help to distribute mushroom harvest effectively and efficiently. The research method consists of defining the problem, collecting data, analyzing systems and implementing methods, designing systems, building systems, and drawing conclusions.